1997
DOI: 10.1002/(sici)1096-8628(19970711)71:1<115::aid-ajmg21>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of aneuploid spermatozoa among infertile men studied by multicolor fluorescence in situ hybridization

Abstract: We studied by fluorescence in situ hybridization the frequency of aneuploidy in spermatozoa of 12 infertile men: 8 with normal or nearly normal semen analysis values and 4 with oligo-astheno-teratozoospermia. The control group consisted of 18 normal healthy fertile men. Probes for chromosome 1 and 7 were used and 10,000 spermatozoa per individual were scored. The hybridization efficiency was good (higher than 98%). In the group with nearly normal semen analysis values the frequencies of spermatozoa disomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(9 citation statements)
references
References 34 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Applying dual and triple colour FISH, several studies have reported a higher frequency of chromosomal aneuploidies in spermatozoa of infertile men compared with normal fertile donors, at least for some chromosomes (Moosani et al, 1995;Pang et al, 1995Pang et al, , 1999Bernardini et al, 1997;Colombero et al, 1997;Lähdethie et al, 1997;Martin et al, 1997;Rives et al, 1998;Storeng et al, 1998;Vegetti et al, 2000). In addition, the issue of whether older men are at an increased risk of producing aneuploid offspring remains unclear, although some studies have shown a slight effect of age on chromosome numbers in spermatozoa (Griffin et al, 1995;Robbins et al, 1995;Kinakin et al, 1997;Rousseaux et al, 1998;Asada et al, 2000;Bosch et al, 2001;Sloter et al, 2004;Rubes et al, 2005;Wyrobek et al, 2006) while other studies could not detect age-related effects on tested chromosomes in sperm McInnes et al, 1998;Luetjens et al, 2002;Dakouane et al, 2005a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Applying dual and triple colour FISH, several studies have reported a higher frequency of chromosomal aneuploidies in spermatozoa of infertile men compared with normal fertile donors, at least for some chromosomes (Moosani et al, 1995;Pang et al, 1995Pang et al, , 1999Bernardini et al, 1997;Colombero et al, 1997;Lähdethie et al, 1997;Martin et al, 1997;Rives et al, 1998;Storeng et al, 1998;Vegetti et al, 2000). In addition, the issue of whether older men are at an increased risk of producing aneuploid offspring remains unclear, although some studies have shown a slight effect of age on chromosome numbers in spermatozoa (Griffin et al, 1995;Robbins et al, 1995;Kinakin et al, 1997;Rousseaux et al, 1998;Asada et al, 2000;Bosch et al, 2001;Sloter et al, 2004;Rubes et al, 2005;Wyrobek et al, 2006) while other studies could not detect age-related effects on tested chromosomes in sperm McInnes et al, 1998;Luetjens et al, 2002;Dakouane et al, 2005a,b).…”
Section: Discussionmentioning
confidence: 99%
“…In normal individuals disomies are around 0.1 % for most autosomes and 0.3 % for chromosome 21 and the sex chromosomes. Increases in sperm aneuploidies in individuals showing oligoasthenoteratozoospermia (OTA) have been reported by many authors [8,10,[78][79][80][81][82][83][84][85][86][87][88][89][90][91]. Furthermore, an increase in aneuploid sperm has been detected in individuals with alterations of any of the basical semen parameters: sperm number [89,92], sperm motility [10] and sperm morphology [80,89,[93][94][95][96][97].…”
Section: Infertile Individuals With a Normal Karyotypementioning
confidence: 99%
“…The purpose of this work was to study the potential contribution of fungicides and common lifestyle exposures (smoking and alcohol) on the frequencies of aneuploid sperm in 32 healthy farmers. Age and sperm concentration were analyzed as potential confounders, because several previous studies [Griffin et al, 1995;Lähdetie et al, 1997;Martin and Rademaker, 1987;Martin et al, 1995;Moosani et al, 1995;Robbins et al, 1995] have suggested an association between these factors and sperm aneuploidy.…”
Section: Introductionmentioning
confidence: 99%